INFLUENCE OF MOTIVATION, COMPETENCE AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. WASKITA KARYA (PERSERO) TBK BENER DAM DEVELOPMENT PROJECT PACKAGE II IN KAB. PURWOREJO, CENTRAL JAVA - Sugianto Sugianto; Abdul Rahman Mus; Jamaluddin Bijang (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The results of this study indicate that: (1) Motivation has a direct effect on employee performance, which is indicated by the value of the regression coefficient is positive and the degree is significantly smaller than the standard significant degree. (2) Competence has a direct effect on employee performance, which is indicated by the value of the regression coefficient being positive and the degree is significantly smaller than the standard significant degree. (3) Compensation has a direct effect on employee performance, which is indicated by the value of the regression coefficient being positive and the degree of significance is smaller than the standard significant degree. (4) Competence motivation and compensation have a unidirectional effect on employee performance together or simultaneously, which is shown by the F arithmetic value which is greater than the F table value.